Gene essentiality, miniature inverted-repeat transposable elements and pigmentation in Porphyromonas gingivalis: Convergence at a unique glycosyltransferase. - Klein, Brian. (2017)
Abstract: Periodontal disease is a bacterially-induced ailment which results in inflammation, destruction of oral structural integrity, loss of teeth and systemic comorbidities. It is a polymicrobial disease in which no single bacterial species is sufficient or necessary to elicit disease. Yet several periodontopathic species such as Porphyromonas gingivalis have been associated with disease occurrence and progression. P. gingivalis is a Gram-negative anaerobic bacterial species with a subgingival oral cavity niche. P. gingivalis elaborates numerous virulence factors that aid in its ability to colonize, evade immune system clearance and cause disease. The most recognizable phenotypic feature, which doubles as an important virulence factor, is black colony pigmentation. Pigmentation of P. gingivalis protects against phagocytosis, UV damage and oxidative damage, and non-pigmented mutants have been shown to be avirulent in animal infection models. Another important virulence feature, on a molecular level as opposed to macroscopic colony pigmentation, is lipopolysaccharide. P. gingivalis can display at least five different lipid-A versions as well as two distinct O-antigen moieties of lipopolysaccharide, which carry different immunomodulatory capabilities. A third virulence feature, on a genetic and genomic level, is a diverse repertoire of mobile and repetitive elements. Intra-strain chromosomal rearrangement and transcriptional modulation have been demonstrated for mobile and repetitive elements in P. gingivalis, and the potential of interstrain and interspecies genetic transfer allows for clone and population-level adaptation. We chose to further investigate the virulence factors of P. gingivalis by adapting and developing transposon mutagenesis using a transposon system and coupling it with sequencing technology for P. gingivalis. After generating the transposon mutant library we characterized the in vitro essential genes of P. gingivalis and began investigating colony pigmentation and tetrapyrrole metabolism. Through screening the library for colony pigmentation defects and selecting the library under variable nutrient conditions we identified a novel miniature inverted-repeat transposable element that has connections to pigmentation and haem metabolism as well as a lipopolysaccharide-affecting gene that is necessary for proper colony pigmentation. Understanding the pathways and mechanisms relating to P. gingivalis colony pigmentation, as well as the genetic elements capable of modulating the genomic and transcriptomic landscape, will allow for better understanding of a keystone periodontopathic species on a basic genetic and metabolic level along with potential for targeted clinical applications.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Linden Hu.; Committee: Andrew Camilli, Michael Malamy, Carol Kumamoto, and Margaret Duncan.; Keywords: Microbiology, Genetics, and Molecular biology.